Islam and colonialism : becoming modern in Indonesia and Malaya - Ali, Muhamad, 1974- (Edinburgh : Edinburgh University Press, 2016)
This text offers a comparative and cross-cultural history of Islamic reform and European colonialism as both dependent and independent factors in shaping the multiple ways of becoming modern in Indonesia and Malaya during the first half of the twentieth century.
Includes bibliographical references and index.
Description based on print version record.
Master record variable field(s) change: 050
Keywords: Islam -- Malaysia -- History -- 20th century; Islam -- Indonesia -- History -- 20th century; Islam -- Relations; Islam and secularism; Interfaith relations; Islam; Islam and secularism; Indonesia; Malaysia; RELIGION -- Islam -- General; RELIGION / Islam / General; 1900-1999; History; Electronic books